The Best Phone Store, Intelligent Recommendation System for Smartphone Selection - Asmawati, Endah; Limanto, Susana; Heru Arwoko; Mario Matthew Cardinal Vincent (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2026)
Abstract— Nowadays, smartphones are a primary item that is needed by almost everyone, from children to adults. The large number of smartphones on the market makes it difficult for consumers to find a smartphone that suits their needs. Each person usually has many considerations (criteria) in choosing the best smartphone for themselves. Each smartphone offers something interesting with different advantages. This often makes prospective buyers confused to choose the right smartphone according to their needs. Many applications have been developed to help prospective smartphone buyers overcome the difficulty of choosing a smartphone, but the smartphone recommendation applications that are developed usually use alternatives stored in a static database, making them less suitable for use in the future, where new smartphones continue to emerge. In addition, the circulating applications do not provide default weight values ​​for the selection criteria. This condition can cause confusion among prospective buyers who have limited smartphone knowledge.